O-003 CLEVER: clinical evaluation of WEB 17 device in intracranial aneurysms. safety results for ruptured and unruptured aneurysm at 30 days. (23rd July 2022) - Spelle, L; Cognard, C; Szikora, I; Costalat, V; Wodarg, F; Herbreteau, D; Fischer, S; Möhlenbruch, M; Papagiannaki, C; Klisch, J; Rautio, R; Numminen, J; et al.
Abstract : Introduction: Intrasaccular flow disruption is an endovascular approach for treatment of wide-neck aneurysms and, more specifically, wide-neck bifurcation aneurysms (WNBA). The WEB device has demonstrated its efficacy and safety, for both unruptured and ruptured aneurysms. The CLEVER objective has been set up to provide safety and efficacy data on the WEB 0.017 device in treatment of bifurcation aneurysms.These results report description of the full population and safety results within 30 days post procedure. Material/Methods: CLEVER study is an observational, prospective and multicenter study conducted in 17 European sites (France, Germany, Hungary, Finland, United Kingdom) using the WEB 0.017 device, the last developed model of WEB product family with a lower profile. The data collected are 100% monitored and the primary endpoints independently evaluated. Patients'data are collected from baseline to 12-month post-treatment with evaluation visits at discharge, 1, 6 and 12-months post-treatment. Occlusion results are assessed independently by a Corelab and adverse events are adjudicated by a Clinical Events Committee. Study design allows to analyze the study results for the full population as well as separately for ruptured and unruptured aneurysm. An intention treat analysis is performed for the safety population, and sample size calculation is based on objective performance approach for safety and efficacy rates. Results: From March 2019 to February 2021, 163 patients (mean age, 58.1 years; 68.1% of women) with 103 unruptured aneurysms and 60 ruptured aneurysms were enrolled.The aneurysms locations were on the ACom (37.4%), the MCA bifurcation (30.1%), the PCom (10.4%), the BA (8.6%), the ICAt (3.7%), the pericallosal artery (3.7%), the ACA (0.6%) and other locations (5.5%). The aneurysms treated were ranging from 2 to 9.2 mm (mean maximum sac width = 5.0 mm). The WEB procedure was completed with success in 163 patients (100%). 147/163 (90.2%) of aneurysm were treated only with WEB implant and adjunctive implant devices were used in 16/163 (9.8%) of cases.For this report covering analysis of data up to 30 days, the primary safety endpoint was the proportion of patients with death of any nonaccidental cause or any major stroke (defined as ischemic or hemorrhagic stroke resulting in an increase of 4 points or more on the NIHSS) within the first 30 days after treatment. Two major strokes on 2/163 patients (1.2%) met the primary safety endpoint. The mortality rate at 30 days was 0%. A detailed description of events reported from per procedure up to 30 days will be provided with a specific attention to the aneurysm initial presentation (ruptured vs unruptured).The 12 months data are not yet available so will not be presented. Conclusion: These results show good safety profile at 1 month, with low rate of neurological or neurovascular event with permanent deficit and no mortality at 30 days. These data confirm the safety of WEB use in intracranial aneurysm treatment, unruptured as well as ruptured, and are consistent with the results published up to date. Disclosures: L. Spelle: 2; C; Microvention, Medtronic, Phenox, Stryker, Balt. C. Cognard: None. I. Szikora: None. V. Costalat: None. F. Wodarg: None. D. Herbreteau: None. S. Fischer: None. M. Möhlenbruch: None. C. Papagiannaki: None. J. Klisch: None. R. Rautio: None. J. Numminen: None. A. Berlis: None. J. Downer: None. M. Bester: None. S. Velasco: None. T. Liebig: None. J. Byrne: None. L. Pierot: None.